Bioavailability and Solubility of Heavy Metals and Trace Elements during Composting of Cow Manure and Tree Litter - Kelvin Reyes Pinto; Víctor Meza-Contreras; Julio César Alegre-Orihuela; Warren Réategui-Romero (Applied and Environmental Soil Science)
Objectives. To characterize the total content of heavy metals (Cd, Cr, Cu, Hg, Mo, Ni, Pb, and Zn) and trace elements (As and Se) of interest, their bioavailability and solubility during the composting of cow manure and tree litter in piles inoculated with beneficial microorganism (IBM), or not inoculated (NBM), on the university campus of the Universidad Nacional Agraria La Molina (UNALM). Methods. The investigation evaluated composting in six piles, three IBM piles and three NBM piles, for 120 days. Every 30 days, a composite sample was taken from each pile. The raw materials used were cattle manure and tree litter. The variables analyzed were the total concentrations (content) of metals and trace elements of interest, extracted with diethylenetriaminepentaacetic acid/pentatetic acid (DTPA) (for the bioavailability study) and extracted with deionized water (for the solubility study). Results. The average values (n = 3) of the total content (mg·kg−1) on day 120 in IBM were in the following order: Zn (404.33) > Cu (86.33) > Pb (71.2) > Cr (34.33) > As (28.0) > Ni (13.83) > Mo (2.86) > Se (1.38) > Cd (1.32) > Hg (0.39) and in NBM: Zn (466.0) > Cu (112.23) > Pb (73.23) > Cr (35.33) > As (29.67) > Ni (14.37) > Mo (3.23) > Se (1.55) > Cd (1.38) > Hg (0.38). The values complied with the Austrian Compost Standard for Landscaping and Land Rehabilitation and the Peruvian Standard for Nonorganic Agriculture. Significant differences were observed in some elements (p < 0.05) between 0 and 120 days in both types of pile (IBM and NBM). Conclusions. For nonorganic agriculture in Peru, urban compost is recommended, whereby raw organic materials are inoculated with beneficial microorganisms during the composting process to reduce the bioavailability of Cu and Zn, as these elements showed less bioavailability than noninoculated piles. The composting process for both piles (IBM and NBM) reduced the solubility in Cu, Pb, and Zn.